2019
DOI: 10.1016/bs.pmbts.2019.05.009
|View full text |Cite
|
Sign up to set email alerts
|

FTD spectrum: Neuroimaging across the FTD spectrum

Abstract: Frontotemporal dementia is a complex and heterogeneous neurodegenerative disease that encompasses many clinical syndromes, pathological diseases, and genetic mutations. Neuroimaging has played a critical role in our understanding of the underlying pathophysiology of frontotemporal dementia and provided biomarkers to aid diagnosis. Early studies defined patterns of neurodegeneration and hypometabolism associated with the clinical, pathological and genetic aspects of frontotemporal dementia, with more recent stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
39
0
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(47 citation statements)
references
References 269 publications
(414 reference statements)
2
39
0
6
Order By: Relevance
“…Hypometabolism on FDG-PET is shown for individual patients, represented as Z score maps depicting abnormalities compared to controls. Adapted with permission from Whitwell 2019 [ 258 ] …”
Section: Neuroimaging Of Frontotemporal Dementia Syndromesmentioning
confidence: 99%
See 1 more Smart Citation
“…Hypometabolism on FDG-PET is shown for individual patients, represented as Z score maps depicting abnormalities compared to controls. Adapted with permission from Whitwell 2019 [ 258 ] …”
Section: Neuroimaging Of Frontotemporal Dementia Syndromesmentioning
confidence: 99%
“…Hypometabolism on FDG-PET is shown for individual patients, represented as Z score maps depicting abnormalities compared to controls. Adapted with permission from Whitwell 2019 [258] effect sizes [143]. Hypometabolism can often be found impacting the frontal lobes, particularly in the medial PFC, dorsolateral PFC, ventrolateral PFC, orbitofrontal cortex, and anterior cingulate cortex [138,144,145].…”
Section: Behavioral Variant Frontotemporal Dementiamentioning
confidence: 99%
“…Classically, FTD cases show frontotemporal and insular atrophy in structural neuroimaging, with Magnetic Resonance Imaging (MRI) ( 104 ). In functional neuroimaging including positron emission tomography (PET) or single-photon emission computed tomography (SPECT), hypometabolism and hypoperfusion have been described ( 105 ), suggesting the involvement of either structural and/or functional impairment of the frontal lobe in the pathogenesis of FTD ( 19 ).…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, several other biomarkers are being used around the world, including functional imaging allowing in vivo imaging of proteins, DTI allowing to evaluate the connection between lobes, among others ( 105 ). They have provided important insights into FTD pathology, especially in HIC ( 104 , 129 ), therefore an effort should also be done to increase the access to those resources for special cases.…”
Section: Resultsmentioning
confidence: 99%
“…Structural MRI studies have revealed the extent of gray matter (GM) atrophy and its impact on the occurrence and development of disease 10‐12 . Moreover, functional connectivity studies using resting‐state functional magnetic resonance imaging (rs‐fMRI) have revealed the changes in brain network 10,13 . However, there are few studies on the changes in local brain activities.…”
Section: Introductionmentioning
confidence: 99%